Anabolic Androgenic Steroid Abuse: The Effects on Thrombosis Risk, Coagulation, and Fibrinolysis - Chang, Simon; Münster, Anna-Marie B.; Gram, Jørgen; Sidelmann, Johannes J. (Seminars in Thrombosis and Hemostasis, 2018)
Anabolic androgenic steroid (AAS) abuse surged during the 1980s and is seen in approximately 1 in 20 of all males today. A wide spectrum of AAS compounds and abuse regimens are applied and AAS abuse has been associated with an unfavorable cardiovascular profile. The aim of this review is to critique the collected data concerning effects of AAS abuse on thrombosis risk through presentation of condensed evidence from studies investigating AAS-induced changes in coagulation, fibrinolysis, and cardiovascular risk markers. AAS abuse inflicts a procoagulant distribution of cardiovascular risk markers including dyslipidemia and atherosclerosis proneness. AAS abuse overall stimulates synthesis of coagulation factors, inhibitors, and fibrinolytic proteins resulting in both increased global coagulation and stimulation of fibrinolysis. Overall, supported by many case reports and some epidemiological studies, AAS abuse is associated with an increased risk of thrombosis. However, to provide clear evidence for a causal relationship between AAS abuse and thrombosis risk, future studies need to address a range of potential biases, insufficient methodology, and other shortcomings of the current literature as highlighted in this review.
Keywords: anabolic androgenic steroids; coagulation; fibrinolysis; thrombosis risk